Literatur Review; Faktor-Faktor Yang Berhubungan Dengan Kejadian Stunting Pada Balita - I Kadek Dwi Swarjana; Kartika Kartika (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
Introduction: Stunting is a problem that hinders human development globally. Currently, around 162 million children under the age of five are stunted. If this trend continues, it is projected that by 2025 there are 127 million children under the age of five who will be stunted. Objectives:  To explain the factors that cause stunting in children under five from the aspects of education, knowledge, maternal attitudes and family economic status, as well as low birth weight. Methods: In writing this literature review, using the method of searching literature from international articles using the ScienceDirect, Goggle Scholar, and ProQuest databases. An initial search using the keywords:” Stunting on a toddler” resulted in 1.300 international articles from 2016, 2017, 2018, 2019  2020 and 2021 that match the inclusion criteria. Results: Based on the results of the literature review, it was found that the relationship between maternal education and the incidence of stunting in children under five found that maternal education greatly determines children's health, knowledge and positive attitudes that are owned by mothers are also factors that cause stunting in toddlers. In addition, the ability of families to meet food needs both in terms of quantity and quality of nutrition greatly affects the nutritional status of children and the birth of babies with low birth weight and babies born prematurely at risk of consistently experiencing stunting. Conclusions: Based on the research review literature, it can be concluded that education, knowledge, maternal attitudes and family economic status, as well as low birth weight, have a relationship with the incidence of stunting in children under five.Keywords: Education, Knowledge, Attitude, Economy, LBW, Stunting